The translation of monologues and dialogues to screen: The case study of women in love (1969) - Lima, Samira Silva de Souza (2024)
Women in Love (1969) is a film adaptation, directed by Ken Russell, of D. H. Lawrence's modern English novel Women in Love (1920). This study analyzes the strategies involved in translating monologues and dialogues to the screen, understanding their impact on the constitution of the filmic narrative structure. First, we investigated the techniques used by the filmmakers in translating monologues and dialogues, and examined how these choices influenced the development of the main characters. Second, we explored the strategies Lawrence employed in elaborating monologues and dialogues within his narrative, focusing on how these techniques build characters who either challenge or attempt to preserve the moral values of their time. This research builds on the strengths of Descriptive Translation Studies (Toury, 1995), considering that the translation process must be studied from a rather analytical and not prescriptive perspective. We also observed the norms (Toury, 1995) which may have worked as constraints to the translation process. In this study, the film adaptation is understood as a form of translation, and it is the focus of investigation, based on Descriptive Adaptation Studies (Cattrysse, 1992, 2014). We adopted a polysystemic perspective of analysis, considering the socio-historical and political aspects of both source and target environments (Even-Zohar, 1990). Finally, we used Narratology Studies (Bal, 2017) to build on our narrative analysis. The results indicate that the filmic narrative rearranges the distribution of the characters’ lines, mostly by eliminating secondary characters and reallocating their dialogue to the primary ones. This strategy seems to more consistently develop the main characters, thereby avoiding the confusion of multiple parallel narratives. The movie places greater emphasis on the romantic relationships involving Gudrun, Gerald, Ursula, Rupert and, to some extent, Hermione, reinforcing their protagonism. Additionally, lengthy philosophical internal dialogues and monologues from the novel were either reduced or eliminated, which accelerated the narrative pace. This approach is effective within the cinematographic medium, especially because this film is influenced by the norms of a different historical period, marked by significant social and moral transformations. The focus on the erotic and subversive relationships among the main characters seems to be an effort to update the narrative’s impact for the target culture.